The Role of Zakat and Waqf for the Development of Micro and Small Enterprises (MSEs) in Gombe State Nigeria - Adamu Abubakar Muhammad; Ikilima Abubakar Shariff (International Journal of Small and Medium Enterprises and Business Sustainability, 2022)
Islamic Financial Institutions of Zakat and Waqf are considered Shariah-compliant institutions that effectively developed and impacted the role of developing Micro and Small Enterprises by sharing similar values, principles, and market activities under the Shariah-compliant business sector. Despite its relevancy, there is still low penetration of these Islamic financial institutions as instruments for business development in Gombe State Nigeria. However, the financing measures of MSEs are essential for societal development and economic growth of any society but receive less attention in the study area. The purpose of this study is to investigate the impact of Islamic Financial Institutions of Zakat and Waqf on the development of MSEs in Gombe State Nigeria. A qualitative methodology was used in the research as a tool for gathering data through the review of relevant literature as primary sources and interviews with pertinent personnel on the topic from various perspectives as secondary sources. The findings justified that the development of MSEs with a significant number of business units and financing from Islamic financial institutions of Zakat and Waqf indicates a positive direction for the promotion and development of MSEs in Gombe State Nigeria. It also recommends that Zakat and Waqf funds can be used as new strategies for creating a partnership with internal and external investors for more effective models and application techniques for financing MSEs and addressing the rate of poverty and unemployment in the study area.